The Formulation of The Goal of Insan Kamil as a Basis for The Development of Islamic Education Curriculum - Nurti Budiyanti; Asep Abdul Aziz; Palah Palah; Agus Salim Mansyur (IJECA (International Journal of Education and Curriculum Application), 2020)
Islamic education curriculum development dynamics need significant attention from educational practitioners to determine its policies following the expected goals. It is known that Islamic education in Indonesia has not been running as expected due to the output that does not have competence and personality in accordance with the spirit of Islam. This research aimed to develop the Islamic education curriculum by reforming the education goal formulation. This was implemented by adapting the concept of Insan Kamil in the Quran into Islamic education curriculum development. A literature study found that the formulation of Insan Kamil's goals not only includes cognitive, affective, and psychomotor aspects but also a solid spiritual realm. Consequently, the goal formulation was considered a solution to the development of Islamic education curriculum in producing Insan Kamil, who has faith, piety, and noble character and always has ma'rifatullah.